2021
DOI: 10.7150/ijbs.63300
|View full text |Cite
|
Sign up to set email alerts
|

The role of N-cadherin/c-Jun/NDRG1 axis in the progression of prostate cancer

Abstract: The dysregulation of androgen receptor ( AR ) signaling is a critical event in the progression of prostate cancer (PCa) and hormone therapy consisting of androgen deprivation (ADT) or AR inhibition is therefore used to treat advanced cases. It is known that N-cadherin becomes upregulated following ADT and can directly induce PCa transformation to the castration-resistant stage (CRPC). However, the relationship between AR and N-cadherin is unclear and may promote better understanding of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…A subsequent decrease in PCa cell proliferation and migration was also observed in response to NDRG1 overexpression. This finding supports earlier studies demonstrating the potent ability of NDRG1 to inhibit invasion and metastatic progression of PCa in vitro and in vivo ( 19 , 23 , 27 , 29 , 33 , 103 , 104 ). As EGF-mediated activation of the abovementioned pathways plays a central role in androgen-independent AR activation ( 116 , 117 , 118 ), this suggests that NDRG1 may suppress the development of androgen resistance in PCa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A subsequent decrease in PCa cell proliferation and migration was also observed in response to NDRG1 overexpression. This finding supports earlier studies demonstrating the potent ability of NDRG1 to inhibit invasion and metastatic progression of PCa in vitro and in vivo ( 19 , 23 , 27 , 29 , 33 , 103 , 104 ). As EGF-mediated activation of the abovementioned pathways plays a central role in androgen-independent AR activation ( 116 , 117 , 118 ), this suggests that NDRG1 may suppress the development of androgen resistance in PCa.…”
Section: Discussionsupporting
confidence: 92%
“…Comparing the endogenous expression of NDRG1 between the three different cell types used (androgen-dependent LNCaP cells and androgen-independent 22Rv1 and C4-2B cells), all had similar endogenous NDRG1 levels and also expressed the AR. Notably, earlier studies have shown that the AR directly regulates NDRG1 transcription by binding to the ARE in the NDRG1 promoter ( 101 , 102 ), with this interaction being mediated by other cofactors, such as c-JUN or MLL5, to promote either positive or negative regulation of NDRG1 ( 103 , 104 ). However, our current findings establish for the first time that NDRG1 interacts with and influences the activation and accumulation of the AR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that epigenetic reprogramming is key for PCa progression [ 29 , 30 ] and that inhibition of the epigenetic regulator EZH2 might effectively overcome ADT resistance [ 2 ]. Our previous study found that epigenetically activating AR/NDRG1 signaling through histone methylation and DNA methylation significantly suppresses CRPC progression [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…qPCR analysis was performed as previously described by our group [ 20 , 21 ]. Total RNA was isolated using TRIzol™ reagent (Invitrogen), and complementary DNA (cDNA) was synthesized through One-Step gDNA Removal and cDNA Synthesis SuperMix (TransGen Biotech, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) analysis qPCR analysis was performed as previously described by us [20,21]. Total RNA was isolated using TRIzol™ reagent (Invitrogen) and Complementary DNA (cDNA) was synthesized through One-Step gDNA Removal and cDNA Synthesis SuperMix (TransGen Biotech, Beijing, China).…”
Section: Clinical Pca Samplesmentioning
confidence: 99%